Self-assembly of poly(L-lactide-co-glycolide) and magnetic nanoparticles into nanoclusters for controlled drug delivery. (15th June 2020) - Zumaya, Alma Lucia Villela; Martynek, Dominik; Bautkinová, Tereza; Šoóš, Miroslav; Ulbrich, Pavel; Raquez, Jean-Marie; Dendisová, Marcela; Merna, Jan; Vilčáková, Jarmila; Kopecký, Dušan; Hassouna, Fatima
Graphical abstract: Highlights: Preparation of a multifunctional controlled drug delivery systems by self-assembly. Self-assembly of PLGA and magnetic nanoparticles into (nano)clusters. Effect of the processing parameters on the size and stability of the clusters. Relationship between the drug release kinetics and clusters properties. Abstract: The possibility to combine nanoparticles (NPs) with different functionalities into nanoclusters of controlled size and kinetic profile of drug release presents a promising route for the preparation of a multifunctional drug delivery system. In this study, to construct controlled drug delivery (nano)clusters, a simple and versatile method based on self-assembly via electrostatic interactions of oppositely charged poly(lactide-co-glycolide) (PLGA) and superparamagnetic iron oxide (IO) NPs was developed. Drug loaded heteroclusters with controlled size of 224 ± 52 nm and Zeta potential of −51 ± 6 mV were produced. Dissolution tests demonstrated an accelerated drug release in the heteroclusters compared to neat PLGA NPs after 24 h. This was correlated with the catalytic effect of IO NPs on the degradation of PLGA matrix. Moreover, the magnetic properties of the heteroclusters were maintained after the dissolution tests. Hence, even after drug release, the heteroclusters can be used for treatment with magnetically mediated hyperthermia.